Darul Hikam Education Conference as a Supplement to the Governance of Islamic Science Education - Dikdik Firman Sidik; Irawan; Tedi Priatna (Global Writing Academica Researching and Publishing, 2023)
This study aims to evaluate the science governance of Islamic education, which is strengthened by the annual activity, the Darul Hikam education conference (DHEC), which is held by the Darul Hikam Bandung college. The method used is a phenomenological type of qualitative research. The data is analyzed philosophically, historically and pedagogically. The results of this study indicate that science governance in Islamic education is a necessity to be adaptive to technological developments, especially the metaverse through the readiness of concepts, human resources, hardware and software, and support from government policies. The 2022 DHEC program discusses how education governance needs to be prepared for changes in digital technology through seminars and calls for papers.